Targeting the ATP Synthase in Staphylococcus aureus Small Colony Variants, Streptococcus pyogenes and Pathogenic Fungi - Martin Vestergaard; Sahar Roshanak; Hanne Ingmer (MDPI AG, 2021)
The ATP synthase has been validated as a druggable target with the approval of the ATP synthase inhibitor, bedaquiline, for treatment of drug-resistant Mycobacterium tuberculosis, a bacterial species in which the ATP synthase is essential for viability. Gene inactivation studies have also shown that the ATP synthase is essential among Streptococci, and some studies even suggest that inhibition of the ATP synthase is a strategy for the elimination of Staphylococcus aureus small colony variants with deficiencies in the electron transport chain, as well as pathogenic fungi, such as Candida albicans. Here we investigated five structurally diverse ATP synthase inhibitors, namely N,N'-dicyclohexylcarbodiimide (DCCD), oligomycin A, tomatidine, resveratrol and piceatannol, for their growth inhibitory activity against the bacterial strains Streptococcus pyogenes, S. aureus and two isogenic small colony variants, as well as the pathogenic fungal species, C. albicans and Aspergillus niger. DCCD showed broad-spectrum inhibitory activity against all the strains (minimum inhibitory concentration (MIC) 2-16 µg/mL), except for S. aureus, where the ATP synthase is dispensable for growth. Contrarily, oligomycin A selectively inhibited the fungal strains (MIC 1-8 µg/mL), while tomatidine showed very potent, but selective, activity against small colony variants of S. aureus with compromised electron transport chain activity (MIC 0.0625 µg/mL). Small colony variants of S. aureus were also more sensitive to resveratrol and piceatannol than the wild-type strain, and piceatannol inhibited S. pyogenes at 16-32 µg/mL. We previously showed that transposon inactivation of the ATP synthase sensitizes S. aureus towards polymyxin B and colistin, and here we demonstrate that treatment with structurally diverse ATP synthase inhibitors sensitized S. aureus towards polymyxin B. Collectively, our data show that ATP synthase inhibitors can have selective inhibitory activity against pathogenic microorganisms in which the ATP synthase is essential. The data also show that the inhibition of the ATP synthase in Streptococcus pyogenes may be a new strategy for development of a narrow-spectrum antibiotic class. In other major bacterial pathogens, such as S. aureus and potentially Escherichia coli, where the ATP synthase is dispensable, the ATP synthase inhibitors may be applied in combination with antimicrobial peptides to provide new therapeutic options.